La concesión de los ferrocarriles en el Perú en el periodo 1826-1879 - Retamozo Linares, Alberto (2024)
In 19th century, the construction of railroads in Peru was associated with pro gress and general welfare, driven by the exploitation of guano and the parti cipation of the private sector through concessions. However, this process was marked by disorderly spending, lack of planning and control, and unlawful conduct. When Manuel Pardo assumed the presidency in 1872, he found that the railroad policy had been a failure, leaving the Treasury without resources. In spite of this, subsequent governments continued with this policy, enacting laws, carrying out studies and granting concessions to contractors such as Enrique Meiggs. The way in which the concessions were handled, the benefits for the proponents and the corrupt behavior led to the failure of the railroad project and the national decline. In short, the idea of progress through the railroads was frustrated by the lack of planning, financial disorder and co rruption in the railroad construction process.